2023
DOI: 10.1155/2023/5469258
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Identification and Analysis of Potentially Bioactive Antiviral Phytochemicals against SARS‐CoV‐2: A Molecular Docking and Dynamics Simulation Approach

Abstract: SARS-CoV-2, a deadly coronavirus sparked COVID-19 pandemic around the globe. With an increased mutation rate, this infectious agent is highly transmissible inducing an escalated rate of infections and death everywhere. Hence, the discovery of a viable antiviral therapy option is urgent. Computational approaches have offered a revolutionary framework to identify novel antimicrobial treatment regimens and allow a quicker, cost-effective, and productive conversion into the health center by evaluating preliminary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…These interactions contributed substantially to the binding potential of compounds 1-10 with 3CL Pro . The non-covalent interaction of compounds 1-10 with 3CL Pro is in agreement with some recent studies in which phytochemicals and herbal medicines have also shown their preferential binding with catalytic dyads that led to the inhibition of 3CL Pro activity in SARS-CoV-2 [29,54,55]. In addition, we found that compounds 2, 3, and 10 showed high negative docking scores (−7.7, −8.0, and −8.2 kcal/mol), which are comparable to the Remdesivir-3CL Pro docking score (−8.2 kcal/mol) [56].…”
Section: Discussionsupporting
confidence: 90%
“…These interactions contributed substantially to the binding potential of compounds 1-10 with 3CL Pro . The non-covalent interaction of compounds 1-10 with 3CL Pro is in agreement with some recent studies in which phytochemicals and herbal medicines have also shown their preferential binding with catalytic dyads that led to the inhibition of 3CL Pro activity in SARS-CoV-2 [29,54,55]. In addition, we found that compounds 2, 3, and 10 showed high negative docking scores (−7.7, −8.0, and −8.2 kcal/mol), which are comparable to the Remdesivir-3CL Pro docking score (−8.2 kcal/mol) [56].…”
Section: Discussionsupporting
confidence: 90%
“…When we compare these scores to existing research using commercial drugs like Paxlovid and molnupiravir, we see that the docking scores with respect to Mpro are −6.4 and −6.6 kcal/mol, while for the ACE2 receptor, it is −7.6 and −7 kcal/mol, respectively. It′s clear that the docking scores for our predicted compounds are lower than those previous scores [45,46] . Figure 3 (a & b) Shows the best docked pose of CoV2 main protease and ACE2 receptor with corresponding antiviral drugs.…”
Section: Resultsmentioning
confidence: 81%
“…The process primarily based on multiple factors such as detection of hydrophobic or hydrophilic interactions, salt bridges and electrostatic and hydrogen bonding interactions. The computed atlas of surface topography of proteins (CASTp 3.0) website ( http://sts.bioe.uic.edu/castp/index.html?3igg ) was exploited to determine the vaccine’s active regions 60 , 61 . The default probe radius of 1.4 ˚A was used.…”
Section: Methodsmentioning
confidence: 99%